Linearity of the ratio of forces-velocity relationship is not related to initial acceleration performance in sprinting - King, D.; Burnie, L.; Nagahara, R.; Bezodis, N. (ISBS Proceedings Archive (Michigan), 2021)
The relationship between the linearity of the ratio of forces (RF)-horizontal velocity (vH) profile and initial acceleration (IA) performance was investigated in trained sprinters. Ground reaction force data from the IA phase of a maximal sprint from a block start were analysed. The coefficient of determination of the linear trendline fitted to four step-averaged values of RF and vH provided a measure of linearity. Semi-partial correlations (sr) accounting for block phase performance revealed a weak negative relationship between linearity of the RF-vH profile and performance over the first four steps (sr = -0.11), while mean RF displayed a very strong positive relationship with performance (sr = 0.80). Sprinters and coaches should therefore prioritise the production of a high RF during IA above trying to ensure a consistent decline in RF as velocity increases.